ANALISIS KEBERHASILAN PENGGUNAAN PERANGKAT LUNAK AKUNTANSI DITINJAU DARI PERSEPSI PEMAKAI (STUDI IMPLEMENTASI MODEL KEBERHASILAN SISTEM INFORMASI) - Istianingsih, Istianingsih; Wijanto, Setyo Hari (Jurnal Akuntansi dan Keuangan Indonesia, 2008)
The purpose o f this study is to examine the information system (IS) success o f the accounting software based on the user perception. The model used to examine the IS success is the modified IS success model ofSeddon (1997). The model employed in this study is applied on data collected through 204 questionnaires distributed to the users o f accounting software who work at the variety o f companies in Indonesia. In examining the model, we employ the Structural Equation Model (SEM) with the use o f LISREL 8.72 sojH>are. The results o f the study show that system quality significantly affects the perceived usefulness and the user satisfaction. Furthermore, the results show that informc\tion quality significantly affects the perceived usefulness and user satisfaction. On the other hand, the study finds that user satisfaction does not affect the system use.